Study of Seed Germination of Common Chicory (Cichorium Intybus L.) - Laziza, Batirova; Eler, Xidirkulov (European Journal of Life Safety and Stability (2660-9630), 2023)
This articleыdiscusses the description, application, chemical composition of the plant, andthe study of seed germination of common Chicory (Cichorium Intybus L.).